0624 Voice of the Patient: A Patient-Centered Exploration of Factors Influencing Obstructive Sleep Apnea Care. (27th May 2020) - Puravath, F M; Ash, T; Rottapel, R; Spadola, C; Bandana, S; Schonberg, M; Redline, S; Bertisch, S
Abstract: Introduction: Despite widely available efficacious treatments for obstructive sleep apnea (OSA), patients commonly report frustration in accessing and adhering to treatments. Sparse research has explored factors influencing OSA care from the patient perspective, which may limit provision of patient-centered care: care responsive to patient preferences, needs, and values. To this end, we conducted qualitative research to identify factors, voiced by patients, that influence OSA treatment initiation and adherence. Methods: We performed semi-structured interviews with 15 patients previously diagnosed with OSA from Boston, MA and a national patient portal (MyApnea.Org). Patients were asked about barriers and facilitators to their diagnosis and treatment as well as about their preferences and values that informed their treatment decisions. Interviews were audio-recorded and transcribed. A qualitative content analysis was performed to identify themes. After developing a codebook, interviews were coded. Codes were then audited and finalized by study team consensus. Results: Our sample was aged 25-74 years; 71% identified as female. Among participants, 57.1% identified as White, 14.3% Black, 14.3% Asian, and 14.3% Other. Major themes were broadly classified as (1) facilitators (provision of useful information on treatment options, participation in shared decision-making, continued clinician support); (2) barriers (inconvenience of treatment, difficulty of habit formation, treatment side effects, competing comorbid conditions); (3) motivators (value of improving chronic health, family support, positive treatment effects); (4) contextual factors (insufficient knowledge/awareness of OSA, navigating healthcare systems, access to informational resources). Awareness of OSA symptoms and treatments, and ongoing support were cited as the most common factors influencing the patient experience. Conclusion: This formative research highlights that diverse factors impact the OSA evaluation and treatment patient experience. Further research should test interventions that promote effective patient-centered care for OSA, such as shared decision-making tools. Support: Brigham and Women's Hospital Research Institute Patient-Centered Comparative Effectiveness Research Center Grant